2017
DOI: 10.1111/1477-9552.12242
|View full text |Cite
|
Sign up to set email alerts
|

The Science of Impact and the Impact of Agricultural Science

Abstract: Research impact and its measurement are of increasing importance. This is particularly significant for agricultural science, which is expected to produce solutions to future challenges that will arise from population growth, climate change and ecosystem degradation. Much econometric effort has been devoted to analysis of investment in agricultural research and its effects on farm productivity. This analysis, reviewed here, has produced a consensus suggesting that returns are high, although they are achieved on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
(42 reference statements)
0
11
0
1
Order By: Relevance
“…The food systems approach places a particular emphasis on outcomes, which is consistent with the "turn" in science governance towards an emphasis on research impact, where policy has attempted to lessen the gap between research and practice. The "European Paradox" suggests that although Europe has been a leading global player in producing highquality scientific output, there has been a failure to translate these scientific advances into tangible economic and industryrelevant impacts (Acosta et al, 2011), with a perception amongst policymakers that the occurrence of impacts are "too few, and poorly targeted with respect to their needs" (Midmore, 2017). Although some commentators question whether this paradox is actually supported by empirical evidence (Dosi et al, 2006), over the last two decades, the need to generate and demonstrate "research impact" has been increasingly emphasised in the European research agenda (Wouters et al, 2015) and in national research agendas (e.g.…”
Section: The Turn To Research Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…The food systems approach places a particular emphasis on outcomes, which is consistent with the "turn" in science governance towards an emphasis on research impact, where policy has attempted to lessen the gap between research and practice. The "European Paradox" suggests that although Europe has been a leading global player in producing highquality scientific output, there has been a failure to translate these scientific advances into tangible economic and industryrelevant impacts (Acosta et al, 2011), with a perception amongst policymakers that the occurrence of impacts are "too few, and poorly targeted with respect to their needs" (Midmore, 2017). Although some commentators question whether this paradox is actually supported by empirical evidence (Dosi et al, 2006), over the last two decades, the need to generate and demonstrate "research impact" has been increasingly emphasised in the European research agenda (Wouters et al, 2015) and in national research agendas (e.g.…”
Section: The Turn To Research Impactmentioning
confidence: 99%
“…With high expectations of accountability for public funding, research funders and society more broadly are requiring researchers to provide evidence of the social, cultural, environmental and economic returns from science (Gibbons, 1999;Bornmann, 2013;Dinsmore et al, 2014). Notwithstanding Midmore's conclusion, following a content analysis of the UK's 2014 REF Impact Case Studies, that researchers have "a nascent conservatism that focuses on research that can be shown to have impact, rather than research impact itself" (Midmore, 2017), providing such evidence is particularly important where food-related research is concerned. Food is at the heart of the SDGs (United Nations, 2015), with more than half of the 17 goals emphasising the need for a safe, nutritious and sustainable food supply (International Food Policy Research Institute [IFPRI], 2016).…”
Section: The Turn To Research Impactmentioning
confidence: 99%
“…As policy makers shift emphasis from measuring production to measuring wellbeing, agricultural economists are well placed to contribute to a wider shift towards wellbeing policies that this is intended to support. Following on from insights in the Presidential Addresses of my two immediate predecessors (Midmore, ; Davis, ), the next section focuses on the particular contribution that growth in knowledge capital can bring to capabilities for personal and communal wellbeing.…”
Section: Sustainability and Wellbeingmentioning
confidence: 99%
“…Over the past decade, research organisations have been challenged to demonstrate the contribution of research and development (R&D) to delivering positive impacts for people, the economy and the environment. This has been in response to an upsurge in public and funder scrutiny of science, shrinking research budgets, and questions regarding what science impacts should be measured and how (Jaffe, 2015; Midmore, 2017; Penfield, Baker, Scoble, & Wykes, 2014). This has overlapped with debates around the nature of the problems that science should be addressing, with an increasing recognition that most challenges – across a range of areas such as natural resource management, food production and health – are fundamentally complex to solve (Schut et al, 2015).…”
Section: Introductionmentioning
confidence: 99%